Annual degradation rates and soiling losses of photovoltaic systems composed of recent crystalline silicon technologies in temperate climate - Tetsuyuki Ishii (Engineering Reports)
Abstract The purpose of this study is to investigate the annual degradation rates of photovoltaic (PV) systems composed of PV modules based on recent crystalline silicon (c‐Si) PV technologies. We investigated the annual degradation rates of four PV systems composed of different c‐Si PV technologies, comprising p‐type multi‐crystalline silicon with a passivated emitter rear cell, n‐type silicon heterojunction, p‐type single‐crystalline silicon (sc‐Si) with an aluminum back surface field, and n‐type (sc‐Si) solar cell technologies. These systems were located in Gunma Prefecture in Japan and were measured over 6 years. Furthermore, the effects of soiling on the annual degradation rates of these PV systems were examined by partially surface cleaning the PV arrays two times. The results obtained indicate that the apparent annual degradation rates of the PV strings before surface cleaning were 0.8, 1.6, 1.4, and 1.2%/year, respectively, because of optical losses due to dust particles. However, the inherent annual degradation rates of the PV strings after surface cleaning were 0.1, 0.6, 0.0, and 0.3%/year, respectively. These low degradation rates indicate that the PV systems composed of the recent c‐Si PV technologies all offered reasonably stable performance that was reduced by 3.6%, 5.5%, 7.3%, and 4.8%, respectively because of the effects of surface soiling, although the surfaces of the PV arrays had been washed by plentiful rainfall under their humid subtropical climatic operating conditions.